Ca3 − x(Fe, Mn)xWO6 (0 < x ≤ 1) prepared from tungsten-containing materials and its leachability in aqueous ammonium carbonate solution. (June 2016) - Li, Xiaobin; Xu, Xiangming; Xu, Wang; Zhou, Qiusheng; Qi, Tiangui; Liu, Guihua; Peng, Zhihong; Cui, Yuanfa; Li, Jianpu
Abstract: The conversion of tungsten-containing materials to a readily soluble substance in ammoniacal solution is significant in the development of a cleaning process for manufacturing ammonium paratungstate. In this work, Ca3 − x (Fe, Mn) x WO6 (0 < x ≤ 1) was prepared by roasting a mixture of tungsten-containing materials and calcium carbonate. The leachability of the roasted products in aqueous ammonium carbonate solution was then tested. Thermodynamic analyses and experimental results showed that Ca2 FeWO6 and Ca2 MnWO6 can be obtained by roasting the mixture with appropriate ingredients in neutral or weakly reducing atmosphere, and Fe(II) in Ca2 FeWO6 can be substituted by Ca to form Ca3 − x Fe x WO6 (0 < x < 1) with an excess of calcium carbonate. With increased roasting temperature and carbon addition, Fe3 W3 C and Mn3 W3 C can be generated. Additionally, leaching results showed that Ca3 − x (Fe, Mn) x WO6 had excellent leachability in aqueous ammonium carbonate solution with 99% WO3 recovery. The results presented can be used to exploit a novel technique with recycling solutions for ammonium paratungstate production. Highlights: Ca2 (Fe, Mn)WO6 was prepared by roasting the mixture of tungsten-containing materials and calcium carbonate. Fe(II) presented in Ca2 FeWO6 could be substituted by Ca to form Ca3 − x Fe x WO6 (0 < x < 1). Ca3 − x (Fe, Mn) x WO6 (0 < x ≤ 1) had excellent leachability in aqueous ammonium carbonate solution.